Human Amniotic Epithelial Cells Cultured in Substitute Serum Medium Maintain Their Stem Cell Characteristics for Up to Four Passages - Evron, Ayelet (Korean Society for Stem Cell Research, 2011)
BACKGROUND AND OBJECTIVES: The common applied culture medium in which human amniotic epithelial cells (hAECs) maintain their stem cell characteristics contains fetal calf serum (FCS) and thus is not compatible with possible future clinical applications due to the danger of animal derived pathogens. To overcome this problem, we replaced FCS with serum substitute supplement, a serum substitute used in the in vitro fertilization for embryo development, in the common applied culture medium and cultured hAECs in this substitute serum medium (SSM). METHODS AND RESULTS: Purity validation and characterization of freshly isolated and cultured hAECs was assessed through the expression of stem cell specific markers by RT-PCR (gene expression), by immunofluorescence staining and FACS (protein expression). Furthermore, karyotype was performed at passage four in order to exclude possible chromosome anomalies in hAECs cultured in SSM. The differentiation potential of hAECs into the cardiomyogenic lineage was tested through cardiac Troponin T expression by immunohistochemistry. hAECs cultured in SSM maintained expression of all the major pluripotent genes Sox-2, Oct-4 and Nanog as well as the expression of the embryonic stem cell specific surface antigens SSEA-4, SSEA-3 and TRA-1-60 over four passages. Using cardiac differentiation medium containing 10% serum substitute supplement, hAECs differentiated into cardiac troponin T expressing cells. CONCLUSIONS: We can conclude that, hAECs maintain their stem cell characteristics when cultured in SSM for up to 4 passages. This makes possible future clinical applications of these cells more feasible.